I am Malala : The Story of the Girl Who Stood Up for Education and was Shot by the Taliban /: The Story of the Girl Who Stood Up for Education and was Shot by the Taliban. (2013) - Yousafzai, Malala, 1997-; Lamb, Christina
No abstract available